2014
DOI: 10.1645/14-532.1
|View full text |Cite
|
Sign up to set email alerts
|

Demodex lutraen. sp. (Acari) in European OtterLutra lutra(Carnivora: Mustelidae) with Data from Other Demodecid Mites in Carnivores

Abstract: This article describes morphological characteristics and occurrence of Demodex lutrae n. sp., which was found on European otter Lutra lutra (Linnaeus, 1758) in Poland. The new species was found in hairy regions of otter skin, mainly in the head area. With respect to morphological features, D. lutrae is most similar to D. canis (Leydig, 1859) from the domestic dog Canis familiaris Linnaeus, 1758. The new species is a medium-sized demodecid mite (adult stages average 200 μm in length); characteristic features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 21 publications
3
18
0
Order By: Relevance
“…However, two species have been described in the domestic cat: D. cati and D. gatoi . Only two species ( D. canis , D. injai ), both found in domestic dogs, have been described as infesting the canine family (Izdebska & Rolbiecki, ), but a third, D. cornei , is confirmed in this study.…”
Section: Discussionsupporting
confidence: 59%
“…However, two species have been described in the domestic cat: D. cati and D. gatoi . Only two species ( D. canis , D. injai ), both found in domestic dogs, have been described as infesting the canine family (Izdebska & Rolbiecki, ), but a third, D. cornei , is confirmed in this study.…”
Section: Discussionsupporting
confidence: 59%
“…canis ? Recently, Izdebska et al [15] found Demodex mites morphologically similar to D . canis in otters ( Lutra lutra ).…”
Section: Discussionmentioning
confidence: 99%
“…D . canis also have been found in cats [5,15,16]. All these mammals are directly related to human activities (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…A new mite species, Demodex lutrae, living in the skin of the head of the European otter (Lutra lutra) was described in Poland in 2014 (27). In 2016, in two males of the gray seal (Phoca vitulina) from a Hungarian zoo, skin lesions caused by an unknown mite of the Demodex species were noticed and effectively treated with amitraz (33).…”
Section: Biology and Morphologymentioning
confidence: 99%
“…The dose for dogs and cats is 6 mg/kg b.w. It is mainly used as a spot-on once a month or, in the case of a severe parasite invasion, every two weeks (27,42). For rabbits, rodents or small mammals, a dose of 6-18 mg/kg b.w.…”
Section: Treatmentmentioning
confidence: 99%